2017
DOI: 10.2196/mhealth.7206
|View full text |Cite
|
Sign up to set email alerts
|

How Do Apps Work? An Analysis of Physical Activity App Users’ Perceptions of Behavior Change Mechanisms

Abstract: BackgroundPhysical activity apps are commonly used to increase levels of activity and health status. To date, the focus of research has been to determine the potential of apps to influence behavior, to ascertain the efficacy of a limited number of apps to change behavior, and to identify the characteristics of apps that users prefer.ObjectiveThe purpose of this study was to identify the mechanisms by which the use of physical activity apps may influence the users’ physical activity behavior.MethodsThis study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Conversely, 'engagement' had the strongest correlation with 'subjective quality' (rho=0.68, p<0.001). This confirms the idea that engagement is an important factor related to sustained app usage [35,37].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Conversely, 'engagement' had the strongest correlation with 'subjective quality' (rho=0.68, p<0.001). This confirms the idea that engagement is an important factor related to sustained app usage [35,37].…”
Section: Discussionsupporting
confidence: 85%
“…Some qualitative studies show that users stop using apps due to hidden costs, increased data entry burden [33], and low perceived engagement [34]. Engagement with an app is generally associated with sustained app usage [1], but it has also been associated with positive changes in physical activity [35,36] and diet [37], fundamental behaviors in weight management.…”
Section: Introductionmentioning
confidence: 99%
“…Apps can provide nutrition education and allow for the setting of dietary goals. Many of these apps have been well received by consumers and facilitate improvements to the predictors of behavior change such as knowledge, self-efficacy and motivation [37,60,[67][68][69][70][71][72]. Being able to be in contact with a healthcare professional also provides a layer of support whenever required, and this has been shown to improve engagement and satisfaction with the lifestyle change [38,58,60,62,63].…”
Section: Benefits Of Digital Healthcare Solutionsmentioning
confidence: 99%
“…Using digital solutions also reduces the burden placed on respondents and healthcare professionals [53,60,67,73]. Many studies have found that users prefer the use of digital dietary recording over traditional paper methods for ergonomic and practical reasons [27,28,37,38,52,58,60,62,67,71,72,74]. Smart devices are highly integrated into modern lifestyles and are less intrusive to daily routines as users do not need to carry around an additional item such as a journal to record their diets with.…”
Section: Benefits Of Digital Healthcare Solutionsmentioning
confidence: 99%
“…It is relatively well-established that usability modifies the degree to which a user perceives a given behavior change technique as central to the efficacy of an app. 23,24 Consequentially, our study is likely biased upward as respondents are likely assuming that apps are highly usable and that they would engage with them regularly.…”
Section: Limitationsmentioning
confidence: 99%